DISPARITAS TUNTUTAN OLEH JAKSA PENUNTUT UMUM TERHADAP PENYALAH GUNA NARKOTIKA DI KEJAKSAAN NEGERI TOBA SAMOSIR - Marlya Retta Bangun; Surya Perdana (JURNAL DOKTRIN REVIEW, 2022)
Criminal disparities have deep consequences for convicts, namely the loss of the convict's sense of justice. In terms of the profession of judges in making decisions, disparity is the freedom given by law to judges to decide cases, freedom is given to judges because the facts of case trials are different from other cases. Meanwhile, on the prosecutor's side, the disparity of demands is also a form of freedom for the Public Prosecutor in processing the perpetrators of criminal acts. The factors causing the disparity in the prosecution of the public prosecutor for the crime are due to errors in the application of the article by the public prosecutor, and the calculation of the qualifications of the defendant's actions, and there is no regulation if the defendant has a dual role as a user or dealer; the impact of criminal disparity brought dissatisfaction to the Defendant and even society in general, as well as social jealousy and negative views by the community. Efforts to reduce the disparity in the demands of the Public Prosecutor at the Toba Samosir District Prosecutor's Office by implementing Guidelines Number 11 of 2021 concerning the Handling of Narcotics Crime Cases and/or narcotics crimes. So that criminal charges are prepared with a special approach, taking into account the qualifications of the crime, the role of the defendant, the type and weight of the evidence, and the casuistic circumstances in a comprehensive and proportional manner.